2000
DOI: 10.1177/1362361300004002005
|View full text |Cite
|
Sign up to set email alerts
|

Greek Teachers’ Perceptions of Autism and Implications for Educational Practice

Abstract: The general aim of this study was to examine perceptions about autism in regular education (n35) and special education (n29) teachers attending the second year of their in-service training. Data were collected through a series of written questions covering four areas of interest (general information, aetiology, behavioural characteristics, treatment). The analysis of findings revealed some confusion in regard to the causes of the syndrome in both groups of teachers. However, special education teachers were mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 7 publications
1
44
0
1
Order By: Relevance
“…This shows that autism does exist among primary school pupils in Yenagoa. This figure may actually be an under estimation of the true picture of autism as many of these children are not accepted in regular schools or are told to withdraw from schools due to their academic backwardness or poor tolerance of these children by their peers and or the teachers 8,9 . A study in Edo state Nigeria, on Autism among primary school pupils in Benin metropolis showed that 22.9% of the respondents acknowledge the existence of autism 9 Although 50% of the respondents who had pupils with traits of autism identified that such a pupil has a developmental disability, there were still another 50% who perceived autism as an evidence of parental neglect, spiritual affliction or a psychiatric condition similar to madness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that autism does exist among primary school pupils in Yenagoa. This figure may actually be an under estimation of the true picture of autism as many of these children are not accepted in regular schools or are told to withdraw from schools due to their academic backwardness or poor tolerance of these children by their peers and or the teachers 8,9 . A study in Edo state Nigeria, on Autism among primary school pupils in Benin metropolis showed that 22.9% of the respondents acknowledge the existence of autism 9 Although 50% of the respondents who had pupils with traits of autism identified that such a pupil has a developmental disability, there were still another 50% who perceived autism as an evidence of parental neglect, spiritual affliction or a psychiatric condition similar to madness.…”
Section: Discussionmentioning
confidence: 99%
“…Accepted that there may be other contributory factors to this poor academic performance, there is an obvious association between the academic performance of these children and the present conventional teaching methods used in regular schools. Studies have shown that when these children are taught in special schools by specially trained teachers using the internationally reviewed methods such as the Applied Behavioural Analysis (ABA) which uses a one-on-one teaching approach that reinforces the practice of various skills, and The Treatment of Autism and Related Communication Handicapped Children (TEACCH), which uses picture schedules and other visual cues that help the child work independently and organize and structure his environment, they do better academically 8 .…”
Section: Discussionmentioning
confidence: 99%
“…These include previous experience of working with children with ASD, family experience, religious or cultural beliefs, the impact of the media or the wider community, and so on (Mavropoulou and Padeliadu, 2000;Bakare et al, 2009b;Imran et al, 2011;Alqahtani, 2012). ASD is often conceptualised negatively throughout Sub-Saharan Africa, with those affected by the condition frequently being considered as 'witches' or 'possessed' (Cimpric, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This poses a very serious problem when taking into consideration the fact that the number of students diagnosed with ASD entering the school districts is increasing. Mavropoulou and Padeliadu (2000) found that there needs to be increased in-service training related to autism for all teachers, whether in special or regular education. Teachers should also have the opportunity to understand the various factors contributing to the needs of each individual child with autism.…”
Section: Teacher Trainingmentioning
confidence: 99%
“…The quality of the teacher student relationship was more dependent on the peer status of the students in the classroom rather than the presence of a paraprofessional (Robertson et aI., 2003). Mavropoulou and Padeliadu (2000) examined regular and special education teachers' knowledge of the causes of autism and the main behavioral features of the disorder. This study explored teachers' views on the goals of treatment for autism, as well as possible differences in the perceptions of the two groups towards autism.…”
Section: Integration Into the General Classroommentioning
confidence: 99%